Challenges Associated with the Adoption of Artificial Intelligence Technologies in the Accounting Profession: The Case of Algeria - Bouabdellah Abdelouahab (Journal of Informatics Education and Research, 2025)
This research aims to examine the applications of artificial intelligence (AI) that have a direct impact on accounting practices and to assess their effectiveness in enhancing the professional efficiency of accountants, while also highlighting the key challenges hindering their adoption within the Algerian accounting environment. To achieve these objectives, the descriptive-analytical method was employed, as it is the most suitable for the nature of the study. The findings revealed that the shift toward digital technologies has become both a strategic option and an urgent necessity across various financial transactions, particularly in accounting activities. This trend has led many major global corporations to rapidly integrate AI solutions into their operations. In this context, Algeria, like other countries, is required to follow these developments and align with the latest advancements in the financial and business world. However, the national legal and accounting frameworks remain insufficiently prepared to meet the requirements of AI integration. Therefore, the current reality underscores the need to adapt economic and accounting legislation to digital and technological transformations in order to ensure the protection of databases and systems against risks of hacking and cyberattacks on the one hand, and to enhance efficiency and effectiveness on the other.